A representação da violência em Um céu de estrelas, de Fernando Bonassi - Jacoby, Graziela Inês (2015)
The Brazilian contemporary narrative is characterized by the multiplicity of styles and themes. There is, however, a recurring element in the prose of the last decades: the representation of violence. Fernando Bonassi is a contemporary writer and is part of a generation of writers that report violence through a brutalist style. The present study has as its object his book Um céu de estrelas (1991) and presents a reading proposal focusing on the representation of violence. We direct our attention to the "narrator" category, seeking to understand how the choice of type of narrator and of the narrative focus consolidates in the text the theme of violence. This study is justified for reflecting some characteristics of contemporary literature and for highlighting issues such as the trivialization of violence, for many situations that are today acknowledged as violence by social sciences, as violence against women, are still seen as natural by a great portion of the population.